A Generation Of 2 Um Q-Switched Thulium-Doped Fibre Laser Based On Anatase Titanium (IV) Oxide Film Saturable Absorber - Abdul Latiff, Anas; M. Rusdi, M. F.; Hisyam, M. B.; Ahmad, H.; Harun, S. W. (Taylor & Francis, 2017)
-